Interpreting Immunoregulation in Lung Fibrosis: A New Branch of the Immune Model - Huaux, François (Frontiers in Immunology, 2021)
Immunostimulation is recognized as an important contribution in lung fibrosis in certain animal models and patient subsets. With this review, we illustrate an additional scenario covering the possible implication of immunoregulatory responses during fibogenesis in absence of inflammation. Available animal and human data indicate that pulmonary fibrosis also includes diverse and discrete immunoregulating populations comprising regulatory lymphocytes (T and B regs) and myeloid cells (immunosuppressive macrophages and myeloid-derived suppressive cells; MDSC). They are initially recruited to limit the establishment of deleterious inflammation but participate in the development of lung fibrosis by producing immunoregulatory mediators (mainly TGF-β1 and IL-10) that directly or indirectly stimulate fibroblasts and matrix protein deposition. The existence of this silent immunoregulatory environment sustains an alternative mechanism of fibrosis that explains why in some conditions neither pro-inflammatory cytokine deficiency nor steroid and immunosuppressive therapies limit lung fibrosis. Therefore, the persistent presence of immunoregulation is an important parameter to consider for refining therapeutical strategies in lung fibrotic disorders under non-inflammatory conditions.